Meningkatkan Keputusan Pembelian Tisu Paseo Melalui Peran Mediasi Citra Merek Di Lottemart Kelapa Gading Jakarta Utara - Nadha Ayu Andini; Parlagutan Silitonga (Human Capital Development, 2022)
This study aims to find out how the role of brand image is a mediating variable between product quality and price perception of purchasing decisions on Paseo wipes at Lottemart Kelapa Gading, North Jakarta. The population in this study was all customers of Lottemart Kelapa Gading. The method used in the research is the quantitative method. This study used primary data obtained from the questionnaire. The sample used in this study was 155 respondents consisting of customers who had purchased at least 2 times using purposive sampling techniques that had been tested for validity and reliability. Data analysis using SmartPLS 3.0. The results of this study show that product quality affects the brand image. Price perception affects purchasing decisions. Product quality affects purchasing decisions. Price perception affects the brand image. Meanwhile, the brand image has no effect on purchasing decisions. On the other hand, product quality and price perception do not affect purchasing decisions through brand image mediation. Keywords: Product Quality, Price Perception, Brand Image, Purchasing Decision